An Assessment of a Public Health Initiative of Homeopathy for Primary Teething - Taneja, Divya; Khurana, Anil; Vichitra, Anil; Sarkar, Sarabjit; Gupta, Arun Kumar; Mittal, Renu; Bawaskar, Ramesh; Sahoo, Amulya Ratan; Prusty, Umakanta; Singh, Shweta; Sharma, Meera; Pant, Richa; Singh, Udaiveer; Upadhyay, Alok Kumar; Sehegal, Shruti; Patnaik, Satyashree; Nath, Tapan; Manchanda, Raj K. (Homeopathy, 2019)
Background During primary teething, children suffer from running nose, mild fever, diarrhoea and other mild irritations and inflammations. A public health programme, ‘Homoeopathy for the Healthy Child’, was undertaken on a pilot basis focusing on promotion of healthy teething by provision of home-based care through six pre-identified homeopathic medicines for complaints commonly observed during primary teething. This article assesses the feasibility of this programme and reports the impact of this initiative on teething profile in children and episodes of diarrhoea and upper respiratory tract infection (URTI).Materials and Methods Accredited Social Health Activists (ASHAs) were trained in child care and usage of a kit comprising six medicines, namely Calcarea phosphoricum 6X (CP), Ferrum phosphoricum 3X, Magnesium phosphoricum 6X, Belladonna 30C, Chamomilla 30C and Podophyllum 30C. Calcarea phosphoricum was given regularly to each participating child from 6 months to 1 year of age. Home-based care for diarrhoea, URTI and mild fever was provided by ASHAs using the other five medicines in the kit. Dentition pattern and diarrhoea/URTI episodes were recorded over a period of the next 12 months.Results Eleven thousand four-hundred and twenty-six children were followed up regularly. Amongst those who enrolled at 6-7 months, a larger proportion of children were approaching expected teething in successive months as compared with children enrolled at 12 months, thus indicating that teething delays, if any, were overcome during this period. Incidence of diarrhoea and URTI showed decrease in the months after enrolment. Children responded favourably to the medicines given by ASHAs at the time of diarrhoea/URTI episodes, and ASHAs expressed satisfaction with the programme.Conclusion An approach with regular use of CP and home-based care with homeopathy through health workers for common problems in teething children is acceptable to the community and enhances outreach of services to the public at large. Observations in terms of the healthy teething period may be further validated through studies of homeopathy with suitable comparator group.
Keywords: Accredited Social Health Activist; Calcarea phosphoricum; children; dentition; diarrhoea; public health; upper respiratory tract infections